Hydraulic–physiological coordination predicts drought recovery: evidence from ten dry–hot valley species - Zhang, Yunchen; Yang, Jianying; Yuan, Xu; Yang, Yandong; Ji, Xiaodong; Ji, Jinnan; Zhang, Yan; Huang, Jiao (Frontiers in Plant Science, 2025)
IntroductionEscalating drought in the Lancang River dry–hot valley demands trait-based rules for selecting planting material that can both persist through prolonged water deficits and rebound after rainfall.MethodsWe conducted a controlled drought–rewatering experiment on ten native species (seven shrubs; three herbs) across a graded soil-water regime and quantified twenty-five functional traits spanning morphology, photosynthesis and photochemistry, biochemistry, hydraulics, and nutrient use.ResultsShrubs generally adopted a conservative strategy, exhibiting more negative xylem pressure at 50% loss of conductivity (P50), wider hydraulic safety margins, and faster recovery of PSII efficiency (Fv/Fm) after rewatering; herbs were more acquisitive, with higher specific leaf area and instantaneous water-use efficiency but reduced hydraulic safety. Trait-network analyses revealed hydraulic variables (P50, specific hydraulic conductivity, and turgor loss point) as central nodes tightly covarying with photosynthetic capacity and antioxidative activity, linking plant water status, carbon gain, and stress metabolism. Under severe drought, rising percent loss of conductivity and increased non-photochemical quenching delineated failure domains in which hydraulic disconnection and photoprotective energy dissipation jointly constrained function. Rewatering improved leaf water status and photochemistry but recovery trajectories were species-specific and retained legacy effects consistent with safety–efficiency trade-offs. Multivariate ordination and integrated scoring separated species into tolerant, intermediate, and sensitive types, with the composite ranking highlighting Rumex hastatus, Caryopteris forrestii, and Sophora davidii as priority candidates that couple high hydraulic safety with resilient photosynthetic recovery.Discussion/ConclusionThese findings show that drought performance in this extreme environment emerges from hydraulic–physiological coordination balancing safety, efficiency, and resilience. Practically, they support a minimal diagnostic panel for rapid screening—P50, turgor loss point, hydraulic safety margin, and post-rewatering Fv/Fm recovery—supplemented by acquisitive leaf traits to resolve strategy space, providing transferable criteria for restoration in drylands facing intensifying hydroclimatic variability.